The battle of Kumanovo in the newspaper „Politika”, as a myth strengthening political position of king Aleksander Karadjordjević - Michalak, Paweł (Balcanica Posnaniensia. Acta et studia, 2012)
Although the commander-in-chief of the Serbian army during both Balkan wars was the chief of staff, general Radomir Putnik, it was his subordinate, a mere 24 years-old Prince Aleksander. The battle of Kumanovo (23rd–24th October 1912), considered as one of the most important battles of the First Balkan War, brought him a great prestige. It seems, that Aleksander tried to strengthen his image as an honest and honorable soldier fighting in defense of his homeland and for the liberation of all South Slavs. It was an effective way of obtaining sympathy subjects, the way, which began to be used on a larger scale after taking the throne by Aleksander Karadjordjević (16th August 1921). The largest and most popular newspaper in the Kingdom of Serbs, Croats and Slovenes (since 1929 Yugoslavia), the daily “Politika” supported the official political line of the king. A very interesting aspect of this activity is its way of presenting events associated with the commemoration of the battle of Kumanovo. The cultivation of the so-called “myth of Kumanovo” was important aspect of king’s Aleksander policy, who in the face of ongoing problems and disputes in the internal policy of the country, wanted to be seen as “unifier”, soldier and hero, who was not interested in political games. Much of his subjects perceived him exactly in that way.